Resistance valves in circulatory loops have a significant impact on in vitro evaluation of blood damage caused by blood pumps: a computational study - Wu, Peng; Bai, Yuqiao; Du, Guanting; Zhang, Liudi; Zhao, Xiangyu (Frontiers in Physiology, 2023)
Background: Hemolysis and its complications are major concerns during the clinical application of blood pumps. In-vitro circulatory testing loops have been employed as the key procedure to evaluate the hemolytic and thrombogenic performance of blood pumps during the development phase and before preclinical in-vivo animal studies. Except for the blood damage induced by the pump under test, blood damage induced by loop components such as the resistance valve may affect the accuracy, reproducibility, and intercomparability of test results.Methods: This study quantitatively investigated the impact of the resistance valve on in vitro evaluation of blood damage caused by blood pumps under different operating points. A series of idealized tubing models under the resistance valve with different openings were created. Three pumps -the FDA benchmark pump, the HeartMate 3 LVAD, and the CH-VAD -were involved in hypothetical tests. 8 operating points were chosen to cover a relatively wide spectrum of testing scenarios. Computational fluid dynamics (CFD) simulations of the tubing and pump models were conducted at the same operating points.Overall, hemolysis and platelet activation induced by a typical resistance valve are equivalent to 17% -45% and 14% -60%, respectively, of those induced by the pump itself. Both ratios varied greatly with flow rate, valve opening and pump models. Differences in blood damage levels between different blood pumps or working conditions can be attenuated by up to 45%. Thus, hemolysis and platelet activation induced by the resistance valve significantly affect the accuracy of 2 This is a provisional file, not the final typeset article in-vitro hemocompatibility evaluations of blood pumps. A more accurate and credible method for hemocompatibility evaluations of blood pumps will benefit from these findings.